1986
DOI: 10.1007/bf00253305
|View full text |Cite
|
Sign up to set email alerts
|

201Tl Myocardial imaging in a cardiac rejection episode

Abstract: Serial myocardial imaging using thallium Tl 201 was performed in the early follow-up of two patients with orthotopic cardiac transplantation. In one patient, non-homogeneous uptake, small defects and an irregular myocardial edge were observed during a moderately acute rejection crisis revealed by endomyocardial biopsy. The abnormal gammagraphic findings and histological changes were coincident and exhibited a parallel reversal. We emphasize the connection between these two events. The mechanisms which could ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…An influence of acute rejection episodes on 201 Tl uptake has been reported [29,30,31]. Although previous studies demonstrated a rapid normalization of coronary flow reserve and 201 Tl scintigraphy [32, 33],former rejection episodes still play a role on the heterogeneity of 201 Tl SPECT, especially in patients with impaired left ventricular function.…”
Section: Discussionmentioning
confidence: 93%
“…An influence of acute rejection episodes on 201 Tl uptake has been reported [29,30,31]. Although previous studies demonstrated a rapid normalization of coronary flow reserve and 201 Tl scintigraphy [32, 33],former rejection episodes still play a role on the heterogeneity of 201 Tl SPECT, especially in patients with impaired left ventricular function.…”
Section: Discussionmentioning
confidence: 93%